La nacionalidad de las personas jurídicas en el arbitraje internacional de inversiones - Puccio Sala, Ricardo (2020)
In this article the treatment of the nationality of legal persons in international investment arbitration will be addressed. Bilateral investment treaties signed by Peru will be analyzed, and a case in which Peru was party will also be discussed.